Cover her face [videorecording (DVD)] - James, P. D.; Fraser, Bill, 1908-1987; Marsden, Roy, 1941-; Calvert, Phyllis, 1915-2002; Davies, John Howard, 1939-2011; James, P. D. (P.D. James the essential collection, 2008)
"A murdered drug dealer, a beautiful witness and a proper country estate. Dalgliesh believes there is a connection"--Koch Entertainment booklet.